Penambahan lama penyinaran dengan perbedaan jam dan jumlah hari pada tanaman krisan (Chrysanthemum sp.) terhadap pertumbuhan dan bobot tanaman - Hanafi Girindra Pratama; Sutarno Sutarno; Adriani Darmawati (Journal of Agro Complex, 2018)
The aims of the research were to analyze light addition at the night to chrysanthemum plant with a difference irradiation length of hours and total of days on growth and weight of plant. This irradiation factor in chrysanthemum plants can affect vegetative growth. The light came from TL lamps with 23 watt of power. The experimental design used was the split block design with the main plot was long irradiation in hours: 1 hour (P1); 2 hours (P2); 3 hours (P3) and 4 hours (P4). While the sub plot was an extension of light in the case of 21 days (H1); 28 days (H2); 35 days (H3) and 42 days (H4). Replication was done 3 times. The results showed the use of irradiation applications above 3 hours and 42 days increased plant height, leaf number, fresh and dry weight of plant. Keywords : Chrysanthemum, irradiation, light.